TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING (TVET): TEMPAT ASAS PEMBINAAN BUDAYA KESELAMATAN DI MALAYSIA - Rosidi Fahlid Mohd Isa (Journal of Vocational Education Studies, 2020)
The purpose of this study was to evaluate occupational safety and health practices among students and lecturers of the Technical Education and Vocational Training Institute (TVET) in Malaysia from the point of view of safety practice, implementation level, compliance and cultural level of occupational safety and health practices. The methodology used in this study uses a quantitative approach. The study was carried out in two parts, Part A was about the personal information of the respondents and Part B was the survey using a questionnaire with respondents from several Technical Education and Vocational Training institutes (TVET) such as Vocational College (KV), Industrial Training Institute (ILP) , National Youth Skills Institute (IKBN) and Mara Skills Institute (IKM). Descriptive statistics tests used to describe occupational safety and health practices, levels of occupational safety and health, occupational safety and health compliance and occupational safety and health culture, found that they applied high level of practice, safety implementation. This means that almost all students and faculty agree that compliance with occupational safety and health practices is of utmost importance and practiced. From this culture of safety practices will create a safe work culture, which will indirectly create a safety culture. An organization that provides a safe environment will benefit workers in their work activities